Breastfeeding and childhood asthma: a six-year population-based cohort study - Jaakkola Jouni JK; Jaakkola Niina; Fredriksson Pia (BMC, 2007)
Abstract Background The question of the protective effect of breastfeeding on development of asthma has raised substantial interest, but the scientific evidence of the optimal duration of breastfeeding is controversial. Methods The authors elaborated the optimal duration of breastfeeding with respect to the risk of asthma primarily, and secondarily to the risk of persistent wheezing, cough and phlegm in school age in a population-based cohort study with the baseline in 1991 and follow-up in 1997. The study population comprised 1984 children aged 7 to 14 years at the end of the follow-up (follow-up rate 77). Information on breastfeeding was based on the baseline survey and information on the health outcomes at the follow-up. Results There was a U-shaped relation between breastfeeding and the outcomes with the lowest risk with breastfeeding from four to nine months for asthma and seven to nine months for persistent wheezing, cough and phlegm. Conclusion Our results suggest a U shape relation between duration of breastfeeding and risk of asthma with an optimal duration of 4 to 6 months. A true concave relation would explain the inconsistent results from the previous studies.